P129 Patient and Physician Demographics in Idiopathic Pulmonary Fibrosis: Results of a UK Physician Survey. (19th November 2012) - Kausar, I; Cameron, R; Eastmond, NC
Abstract : Introduction and Objectives: Idiopathic pulmonary fibrosis (IPF) is a rare, progressive, fibrotic lung disorder of unknown origin, which leads to difficulty in breathing, functional disability and death. Due to symptomatic similarities with other lung conditions, IPF is difficult to diagnose, and patients experience varying standards of care. We undertook a survey of European pulmonologists to gain additional understanding of the characteristics of patients with IPF and the demographics of the physicians treating them. Methods: In December 2010–January 2011, a quantitative survey was conducted with lung specialists in IPF and non-IPF specialist centres in five principal EU countries (Germany, Italy, Spain, UK, France [5EU]). The survey was extended to a further five countries where fewer physicians were targeted. UK data are reported here. Results: The total number of patients seen by all the centres in the survey in the preceding 12 months was 7, 302, 149 of which were from the UK. Among the UK patients, 87% were aged ≤85 years, which is similar to the value for 5EU (85%). Sixty percent of newly diagnosed UK patients were aged 65–80 years (5EU=56%), in contrast to 50% of the whole UK sample (5EU=57%). In 5EU, 70% of IPF patients were managed by 35% of pulmonologists, in contrast to the UK where 80% of patients were managed by 55% of pulmonologists. In the UK, 70% of pulmonologists were seeing fewer than 110 IPF patients annually, whereas in the 5EU, 70% of pulmonologists were seeing <30 IPF patients annually. Regional differences in the UK largely reflect population distribution with 14% of Scottish pulmonologists seeing ≥30 IPF patients, versus 33% for the north of England, 24% for the Midlands and Wales, and 29% for the south of England. Conclusion: In the UK, patient demographics for IPF were similar to the rest of Europe, but UK patients were being diagnosed at a younger age than previously compared to the rest of the EU. Importantly, the UK had a much wider spread of IPF patients among treating pulmonologists than the rest of Europe, which indicates a greater distribution of expertise in treating the disease.